The front-loading problem in presidential nominations - Mayer, William G., 1956- (Brookings Institution Press, 2004)
Front-loading is the single most criticized feature of the American presidential selection process. This text addresses the front-loading problem, providing a comprehensive examination of the entire issue: what it is, when and why it was developed, and its consequences for the nomination process.